A Survey of Prescription Errors in Paediatric Outpatients in Multi-Primary Care Settings: The Implementation of an Electronic Pre-Prescription System - Tan, Lu; Chen, Wenying; He, Binghong; Zhu, Jiangwei; Cen, Xiaolin; Feng, Huancun (Frontiers in Pediatrics, 2022)
Background Prescription errors impact the safety and efficacy of therapy and are considered to have a higher impact on paediatric populations. Nevertheless, information in paediatrics is still lacking, particularly in primary care settings. There exists a need to investigate the prevalence and characteristics of prescription errors in paediatric outpatients to prevent such errors during the prescription stage. Methods A cross-sectional study to evaluate paediatric prescription errors in multi-primary care settings was conducted between August 2019 and July 2021. Prescriptions documented within the electronic pre-prescription system were automatically reviewed by the system and then, potentially inappropriate prescriptions would be reconciled by remote pharmacists via a regional pharmacy information exchange network. The demographics of paediatric patients, prescription details, and types/rates of errors were assessed and used to identify associated factors for prescription using logistic regression. Results A total of 39,754 outpatient paediatric prescriptions in 13 community health care centres were reviewed, among which 1,724 prescriptions (4.3%) were enrolled in the study as they met the inclusion criteria. Dose errors were the most prevalent (27%), with the predominance of underdosing (69%). They were followed by errors in selection without specified indications (24.5%), incompatibility (12.4%), and frequency errors (9.9%). Among critical errors were drug duplication (8.7%), contraindication (.9%), and drug interaction (.8%) that directly affect the drug's safety and efficacy. Notably, error rates were highest in medications for respiratory system drugs (50.5%), antibiotics (27.3%), and Chinese traditional medicine (12.3%). Results of logistic regression revealed that specific drug classification (antitussives, expectorants and mucolytic agents, anti-infective agents), patient age (<6 years), and prescriber specialty (paediatrics) related positively to errors. Conclusion Our study provides the prevalence and characteristics of prescription errors of paediatric outpatients in community settings based on an electronic pre-prescription system. Errors in dose calculations and medications commonly prescribed in primary care settings, such as respiratory system drugs, antibiotics, and Chinese traditional medicine, are certainly to be aware of. These results highlight an essential requirement to update the rules of prescriptions in the pre-prescription system to facilitate the delivery of excellent therapeutic outcomes.